Efektivitas Pelatihan Kelompok Mindful Parenting Secara Daring Terhadap Parenting Stress Dan Parent Self-Efficacy Pada Ibu Rumah Tangga Dengan Anak Usia Dini - Rifat, Daryan Nur; Ratnasari, Yudiana (Universitas Nusantara PGRI Kediri, 2023)
T This study aims to see how effective online Mindful parenting (MP) in reducing parenting stress and increasing parenting efficacy. In addition, it also discusses how MP can reduce parenting stress and increase parenting efficacy for housewives when caring for early childhood. This study uses a qualitative method. The research subjects consisted of seven housewives (non-working) aged 26-32 years, had at least one early childhood, lived in several different cities, and had moderate to severe levels of parenting stress. Research subjects were given a pre-post test using the Interpersonal Mindfulness in Parenting Scale (IM-P), Parenting Stress Scale (PSS), and Parenting Sense of Competence (PSOC) to see comparisons of parenting stress levels, parenting efficacy and parenting mindfulness before and after being given intervention. The results of this study indicate that decrease in parenting stress levels and an increase in parenting efficacy. The study subjects also said that they could control their emotions by pausing before reacting, so as not to perform automatic parenting reactions to their children.